2017
DOI: 10.1016/j.kjms.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of skin wound healing by low‐dose indirect ionizing radiation in male rats

Abstract: A recent hypothesis has revealed that low-dose irradiation (LDI) with ionizing radiation might have a promoting effect on fracture healing. The aim of this study was to investigate the influence of direct (electron beam) and indirect (gamma-ray) low-dose ionizing irradiations on the wound healing process in male rats. In 72 male rats, a full-thickness wound was incised. The animals were randomly assigned to three groups, each with 24 rats. The first two groups were named IG-I and IG-II and respectively exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…23,24 More recent studies have reported an accelerated healing of bone fractures with single doses (0.5 Gy) of X-rays in male Sprague-Dawley rats. 32 Similarly, Jabbari et al 33 reported that a single dose of γ-rays (0.75 Gy) immediately after surgery significantly accelerated the healing process for a full-thickness wound in male Sprague-Dawley rats. Supporting this possibility was an experimental study by Kataoka et al 34 in which a single 0.25 Gy exposure significantly enhanced liver catalase activity in adult mice 24 h after exposure.…”
Section: Resultsmentioning
confidence: 98%
“…23,24 More recent studies have reported an accelerated healing of bone fractures with single doses (0.5 Gy) of X-rays in male Sprague-Dawley rats. 32 Similarly, Jabbari et al 33 reported that a single dose of γ-rays (0.75 Gy) immediately after surgery significantly accelerated the healing process for a full-thickness wound in male Sprague-Dawley rats. Supporting this possibility was an experimental study by Kataoka et al 34 in which a single 0.25 Gy exposure significantly enhanced liver catalase activity in adult mice 24 h after exposure.…”
Section: Resultsmentioning
confidence: 98%
“…The relationship between low doses of radiation and wound healing, however, is not straightforward. Depending on factors such as the duration of exposure, the severity of the wound, and the individual’s overall health, low doses of radiation could either positively or negatively affect wound healing [ 21 , 82 , 83 , 84 ]. The findings from this study in HMEC-1, a group of human dermal microvascular ECs, may encourage further research to investigate the effects of acute exposure to low doses of radiation on angiogenesis in wounds and the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that tissue repairing might be enhanced by low dose irradiation through up-regulation of the level of VEGF (12). Jabbari concluded that gamma-ray irradiation is effective for the acceleration of wound healing (13). However, there is no basic or clinical research of low-dose radiation in the treatment of pressure ulcer.…”
Section: Discussionmentioning
confidence: 99%